Effect of a workplace-based learning program on clerkship students’ behaviors and attitudes toward evidence-based medicine practice - Hajime Kasai; Go Saito; Kenichiro Takeda; Hiroshi Tajima; Chiaki Kawame; Nami Hayama; Kiyoshi Shikino; Ikuo Shimizu; Kazuyo Yamauchi; Mayumi Asahina; Takuji Suzuki; Shoichi Ito (Medical Education Online)
In clinical clerkship (CC), medical students can practice evidence-based medicine (EBM) with their assigned patients. Although CC can be a valuable opportunity for EBM education, the impact of EBM training, including long-term behavioral changes, remains unclear. One hundred and nine fourth- and fifth-year medical students undergoing CC at a medical school in Japan attended a workplace-based learning program for EBM during CC (WB-EBM), which included the practice of the five steps of EBM. The program’s effect on the students’ attitudes toward EBM in CC was assessed through questionnaires. A total of 88 medical students participated in the program. Responses to the questionnaire indicated high satisfaction with the WB-EBM program. The most common theme in students’ clinical problems with their assigned patients was the choice of treatment, followed by its effect. Based on the responses in the post-survey for the long-term effects of the program, the frequency of problem formulation and article reading tended to increase in the ‘within six months’ group comprising 18 students who participated in the WB-EBM program, compared with the control group comprising 34 students who did not. Additionally, the ability to self-assess problem formulation was significantly higher, compared with the control group. However, among 52 students who participated in the WB-EBM program more than six months later, EBM-related behavioral habits in CC and self-assessments of the five steps of EBM were not significantly different from those in the control group. The WB-EBM program was acceptable for medical students in CC. It motivated them to formulate clinical questions and enhanced their critical thinking. Moreover, the WB-EBM program can improve habits and self-evaluations about EBM. However, as its effects may not last more than six months, it may need to be repeated across departments throughout CC to change behavior in EBM practice.